POSTTRAUMATIC STRESS Theoretical models, typology and ethnocultural aspects (Annual of the Faculty of Philosophy in Skopje, 2010)
Trauma survivors experience a continuous “battle” between intrusive thoughts and emotions associated with the trauma and numbness or avoidance of every recollection of the trauma. Theoretical models of development of posttraumatic stress offer complementary explanations for the occurrence of different types of posttraumatic responses. Insight of ethnocultural characteristics of posttraumatic consequences is essential for their effective assessment and treatment.
Keywords: POSTTRAUMATIC STRESS; TRAUMA; POSTTRAUMATIC STRESS DISORDER